Polymerization of Purified Yeast Septins: Evidence That Organized Filament Arrays May Not Be Required for Septin Function - Frazier, Jennifer A. (The Rockefeller University Press, 1998)
The septins are a family of proteins required for cytokinesis in a number of eukaryotic cell types. In budding yeast, these proteins are thought to be the structural components of a filament system present at the mother–bud neck, called the neck filaments. In this study, we report the isolation of a protein complex containing the yeast septins Cdc3p, Cdc10p, Cdc11p, and Cdc12p that is capable of forming long filaments in vitro. To investigate the relationship between these filaments and the neck filaments, we purified septin complexes from cells deleted for CDC10 or CDC11. These complexes were not capable of the polymerization exhibited by wild-type preparations, and analysis of the neck region by electron microscopy revealed that the cdc10Δ and cdc11Δ cells did not contain detectable neck filaments. These results strengthen the hypothesis that the septins are the major structural components of the neck filaments. Surprisingly, we found that septin dependent processes like cytokinesis and the localization of Bud4p to the neck still occurred in cdc10Δ cells. This suggests that the septins may be able to function in the absence of normal polymerization and the formation of a higher order filament structure.